1994
DOI: 10.1111/j.1540-8159.1994.tb01364.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Thrombogenicity of Pacemaker Leads

Abstract: To evaluate the thrombogenicity of transvenous silicone and polyurethane pacemaker leads, 9 of 12 anesthetized Yorkshire pigs (27-32 kg) were implanted with silicone (n = 5) or polyurethane (n = 4) pacemaker leads via a femoral vein. The remaining three pigs served as controls. All 12 pigs were injected with autologous indium-111 labeled platelets (300-420 muCi) 24 hours before anesthesia induction. The pigs were monitored for 3 hours under a gamma camera. Radioactivity in blood and lead segments was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 12 publications
2
30
0
2
Order By: Relevance
“…In a previous animal study, assessing leads in the right ventricle, the mean density of platelet deposits on silicone leads appeared more pronounced on silicone leads compared to polyurethane leads. Our study results are consistent with this study, which demonstrated a relative thromboresistance of polyurethane leads 9 …”
Section: Discussionsupporting
confidence: 94%
“…In a previous animal study, assessing leads in the right ventricle, the mean density of platelet deposits on silicone leads appeared more pronounced on silicone leads compared to polyurethane leads. Our study results are consistent with this study, which demonstrated a relative thromboresistance of polyurethane leads 9 …”
Section: Discussionsupporting
confidence: 94%
“…Using this model, we have demonstrated significantly lower thrombus weights and infusion pressures for polyurethane catheter material as compared to silicone catheters. The observed differences between polyurethane and silicone catheter material in this in vitro model , indicating the silicone catheter tested here is more thrombogenic than the polyurethane catheter, are consistent with relative thrombogenicity of similar materials observed both in vitro and in vivo in most . but not all, previous reports comparing the thrombogenicity of these two materials.…”
Section: Discussionsupporting
confidence: 89%
“…5 In this context, when careful postprocedural anticoagulation is adhered to, there have been no reported cases of thromboembolism in published series. 7 In addition, endocardial pacing has some potential advantages over epicardial pacing, including lower chronic pacing thresholds with resulting increased battery longevity, as well as a reduction in pacing-induced QT dispersion. 7 In addition, endocardial pacing has some potential advantages over epicardial pacing, including lower chronic pacing thresholds with resulting increased battery longevity, as well as a reduction in pacing-induced QT dispersion.…”
Section: Discussionmentioning
confidence: 99%